Meningkatkan Motivasi Belajar Informatika Kelas VII dengan Notion: Media Pembelajaran Berbasis Website : Penelitian - Rasif Nidaan Khofia Ahmadah; Syaad Patmanthara; Putri Alivia Nabila; Rahmadita Sugma Ryanti; Lailatus Sa’adah; Rachman Kurniawa (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This study aims to investigate the improvement of students’ learning motivation through cycles of Classroom Action Research (CAR) by integrating Notion as an interactive learning medium, particularly in the context of data analysis learning. The background of this research stems from the low motivation observed among students in learning data analysis, thereby necessitating an appropriate solution involving the use of digital media, effective teaching methods, and suitable instructional approaches. The method employed in this study follows a classroom action research design, with data analyzed quantitatively. The findings reveal that the use of Notion as a learning tool, when combined with the appropriate pedagogical strategies, significantly enhances students’ motivation to learn. Furthermore, the implementation of this media has the potential to be expanded for broader classroom applications. In conclusion, this study contributes to the development of innovative learning practices and may serve as a valuable reference for future educational research.